PENERAPAN METODE ROLE PLAYING UNTUK MENINGKATKAN PEMAHAMAN JENIS-JENIS USAHA YANG DIKELOLA SECARA KELOMPOK - Sari, Novita; Apriani, Suci Yanur (Jurnal Inovasi dan Teknologi Pendidikan, 2024)
The low results of student evaluation with the results of 6 people getting scores above KKM and 19 people below KKM, is the background of learning improvement to improve understanding of the types of businesses managed in groups in class V Madrasah Ibtidaiyah Undrus by applying the role playing method. Improvement research uses qualitative and quantitative methods with an approach to research consisting of 2 cycles, each cycle consists of planning, implementation, observation and reflection stages. The results showed that teacher performance improved from precycle to cycle one and to cycle two. Student activity also increases every cycle. The test results of students with an average value of cycle 1 before 70.02 increased in cycle 2 to 82.56, the number of students declared complete in cycle 1 as many as 10 students and in cycle two as many as 25 people with a percentage of completeness of 100%. Based on the acquisition of data, learning improvement research is stated to be able to increase students' understanding of the types of businesses managed in groups